PENGARUH STRES KERJA DAN LINGKUNGAN KERJA TERHADAP TURNOVER ITENTION PADA KARYAWAN OPPO KOTA BIMA - Ainayah Oksa Dwiyanthi; Muhammad Yusuf (INVOICE : JURNAL ILMU AKUNTANSI, 2020)
This study aims to determine and analyze the effect of work stress and the environment on turnover attention of employees of Oppo Kota Bima. The type of research used is associative, with a sample of 35 respondents. The sampling technique used was purposive sampling. Data collection using a questionnaire with a Likert scale. The data analysis method used is validity test, reliability test, simple linear regression, simple correlation, determination test and t test (two parties). The results of this study conclude that the workload has an influence on the work environment of the Bima City oppo employees, where the t value of 8.325 is greater than the t table value of 2.036 (8.325 2.036) with a significant value of 0.000 less than 0.05 ( 0,000,0,05).